2016
DOI: 10.1044/2016_ajslp-14-0165
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phonotactic Probability and Neighborhood Density on Adults' Word Learning in Noisy Conditions

Abstract: Purpose: Noisy conditions make auditory processing difficult. This study explores whether noisy conditions influence the effects of phonotactic probability (the likelihood of occurrence of a sound sequence) and neighborhood density (phonological similarity among words) on adults' word learning. Method: Fifty-eight adults learned nonwords varying in phonotactic probability and neighborhood density in either an unfavorable (0-dB signal-to-noise ratio [SNR]) or a favorable (+8-dB SNR) listening condition. Word le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
(89 reference statements)
2
11
2
Order By: Relevance
“…Stimuli were divided at the median value for ND: Words above the median were classified as dense, and words at or below the median value were classified as sparse. This methodology is consistent with related work (e.g., Han et al 2016;Storkel 2001). Sparse words had a mean ND of seven neighbors (sd = 2.94; range = 3-10), and dense words had a mean ND of 23 neighbors (sd = 7.39; range = 16-32).…”
Section: Stimulisupporting
confidence: 90%
See 2 more Smart Citations
“…Stimuli were divided at the median value for ND: Words above the median were classified as dense, and words at or below the median value were classified as sparse. This methodology is consistent with related work (e.g., Han et al 2016;Storkel 2001). Sparse words had a mean ND of seven neighbors (sd = 2.94; range = 3-10), and dense words had a mean ND of 23 neighbors (sd = 7.39; range = 16-32).…”
Section: Stimulisupporting
confidence: 90%
“…Previous similar studies have reported a greater advantage of learning dense nonwords rather than sparse nonwords. However, many of these studies administered tasks originally designed for use with young, preliterate children (Freedman 2015;Han et al 2016;Storkel et al 2006;Dumay and Gaskell 2006;Gaskell and Dumay 2003), which are not ecologically valid for typical adult word learning contexts. This is particularly true in higher education, where adults acquire new lexical items in the context of related information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional factor that potentially could influence children's selections was the possibility that, although features were controlled, the two substitutes were phonetically similar to the accurate phonemes. To ensure that this was not a factor, we determined the confusability between the accurate initial phoneme and each misarticulated phoneme, in accordance with the procedures in Han, Storkel, Lee, and Cox (2016). From the tables in Wang and Bilger (1973), we found the proportion of times each accurate phoneme was confused with the misarticulated phoneme.…”
Section: Auditory Stimulimentioning
confidence: 99%
“…A word learning study by Han, Storkel, Lee, and Cox (2016) revealed that word learning by young adults requires multiple cues of word characteristics to facilitate word learning in noisy learning environments compared to quiet environments.…”
mentioning
confidence: 99%